2019
DOI: 10.1021/acssuschemeng.9b03739
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Identification and Evolution Mechanism of Thermolysis-Driven Gas Emissions from Cathodes of Spent Lithium-Ion Batteries

Abstract: Spent lithium-ion batteries (LIBs) typically contain a combination of both strategic materials and toxic chemicals that cannot be easily disposed. Nowadays, that are many different methods used to treat spent LIBs with the primary aim of critical metals recovery; nevertheless, as a result of the toxic chemicals within the battery waste, the chemical composition and potential danger of the off-gases generated during recycling process have become a serious concern. In an attempt to further understand the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 41 publications
0
39
0
Order By: Relevance
“…Contrarily, the use of heavy metals such as cobalt, manganese or nickel in Li–S batteries is not required, where cathodes use sulfur quantities as large as 70% by weight. This also leads to lower fresh water aquatic ecotoxicity and human toxicity potentials associated with Li–S batteries because LIBs rely on the use of toxic cathodes ( Chen et al., 2019 ). It should be also taken into account that usually, Li–S cathodes are obtained after the introduction of sulfur into a carbonaceous structure by efficient thermal infusion ( Pang et al., 2019 ), avoiding complex, expensive and environmentally harmful synthetic procedures typically of layered oxides used for LIBs and NIBs.…”
Section: Resultsmentioning
confidence: 99%
“…Contrarily, the use of heavy metals such as cobalt, manganese or nickel in Li–S batteries is not required, where cathodes use sulfur quantities as large as 70% by weight. This also leads to lower fresh water aquatic ecotoxicity and human toxicity potentials associated with Li–S batteries because LIBs rely on the use of toxic cathodes ( Chen et al., 2019 ). It should be also taken into account that usually, Li–S cathodes are obtained after the introduction of sulfur into a carbonaceous structure by efficient thermal infusion ( Pang et al., 2019 ), avoiding complex, expensive and environmentally harmful synthetic procedures typically of layered oxides used for LIBs and NIBs.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, a black mass is typically leached in mineral acid. For this purpose, it is beneficial to conduct the thermal pretreatment as described easing the dissolution process [26]. Here, Shin et al report the binder´s (polyvinylidene fluoride, PVDF) property of not dissolving in acidic solution and disturbing the filtration process after leaching [27].…”
Section: Lithium Behavior In Pyro-and Hydrometallurgical Recycling Steps and Need For Early-stage Li-separationmentioning
confidence: 99%
“…Therefore, to solve the problem of excessive leachant consumption, the separation of cathode and anode materials before hydrometallurgical processes is highly recommended. However, it is still rather challenging to achieve a complete separation of anode and cathode materials in an industrial scale [22,54]. Fortunately, He et al demonstrated that the effective separation between anode and cathode materials can be achieved by Fenton assisted flotation.…”
Section: Hydrometallurgical Methodsmentioning
confidence: 99%